2019
DOI: 10.1016/j.dci.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

WSV181 inhibits JAK/STAT signaling and promotes viral replication in Drosophila

Abstract: The Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway plays a critical role in host defense against viral infections. Here, we report the use of the Drosophila model system to investigate the modulation of the JAK/STAT pathway by the white spot syndrome virus (WSSV) protein WSV181. WSV181 overexpression in transgenic flies resulted in the downregulation of STAT92E and STAT92E-targeted genes. This result indicates that WSV181 can suppress JAK/STAT signaling by controlling STAT92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…[26][27][28]38,39 However, there is still little evidence defining the role of LINC00511 in EMT. [26][27][28]38,39 However, there is still little evidence defining the role of LINC00511 in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28]38,39 However, there is still little evidence defining the role of LINC00511 in EMT. [26][27][28]38,39 However, there is still little evidence defining the role of LINC00511 in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, by comparing sterile-bred and conventionally bred animals, Buchon et al (2009a) demonstrated that contact between conventional microorganisms and commensal bacteria can also activate basal levels of Upd expression and subsequent intestinal epithelium renewal at a lower rate through the JAK/STAT pathway (Lee, 2009). Recent studies have found that the JAK/STAT pathway plays a vital role in the host defense against viral infection (Souza-Neto et al, 2009;Morin-Poulard et al, 2014;Wang et al, 2019b). In addition, Upd3 production and JAK/STAT pathway activation in the intestine must also depend on the oxidative burst of Duox (Royet, 2011).…”
Section: Role Of the Jak/stat Signaling Pathway On Intestinal Microor...mentioning
confidence: 99%
“…vannamei , resulted in less WSSV infection 50 . More recently, Wang, W. et al ., 2019 reported that inhibition of the JAK/STAT pathway in Drosophila by WSV181 could enhance WSSV replication 51 . These findings indicated that the JAK/STAT pathway could function as anti-viral response.…”
Section: Discussionmentioning
confidence: 99%